Desenvolvimento de capacidades dinâmicas em subsidiárias de P&D: um estudo exploratório no Instituto Nokia de Tecnologia (INdT) - Viana, Rodrigo Bahia de Cerqueira (2013)
The development of research activities in subsidiaries of multinationals may be a component of their global strategy for entering new markets, by aggregating local characteristics to the products of these companies. Following this strategy, global companies would reuse some of the technologies developed in the headquarter but are also capable of generating patents through projects of R&D (Research and Development) conducted in subsidiaries. This study analyzed the process of capacity development in a dynamic R&D subsidiary, the Nokia Institute of Technology (INdT), located in Manaus (Brazil). The analysis is conducted through the framework of dynamic capabilities because there it was identified a constant process of reconfiguration of resources and expertise was designed to enable INdT to execute R&D activities in an extremely dynamic market, telecommunications. Moreover, this is considered an exploratory study, since there are still relatively rare references regarding similar subsidiaries in Brazil who have reached a significant intellectual production and global. The study used the model of dynamic capabilities to evaluate the process of organizational learning, based on the works of Teece and Zollo (2002) and Pisano (2000) that aim to study the leraning through the R&D activities performed by INdT. Then it s studied the network of partnerships established by the Institute with universities and companies, assessing how this collaboration network relates to the process of organizational learning. Finally, it s analyzed the information exchange with the matrix, trying to understand what knowledge transfer strategies were adopted. This study identified several activities designed to deliberately reconfigure internal resources and intellectual assets INdT in order to enable it to learn new technologies and execute P&D projects involving these technologies. The analysis of the various dimensions of learning revealed that there was a complex process of evolution of skills, involving parallel initiatives and possibly unrelated to each other, demonstrating the variety of possible ways to boost learning, consolidate dynamic capabilities and enable innovation